2016
DOI: 10.15376/biores.11.3.6137-6150
|View full text |Cite
|
Sign up to set email alerts
|

Development of Method to Determine the Concentration of Alkali-Soluble Lignin using Coomassie Brilliant Blue G-250

Abstract: A new method involving the non-covalent binding of Coomassie Brilliant Blue G-250 (CBBG) to alkali-soluble lignin was developed. The binding of the dye to alkali-soluble lignin caused an increase in visible absorption at the maximum wavelength of 630 nm or 640 nm. A linear correlation of the absorbance at their maximum absorbing peak with alkali-soluble lignin concentration was observed. Lignin estimation in black liquor showed that the result of the new method and the gravimetric methods after acidification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…3). This indicated that the increase in absorbance at 640 nm in the newly prepared mixtures of alkali lignin solution and CBBG was from a combination of CBBG and lignin; which was consistent with non-covalent combination between the lignins and the CBBG to increase the absorption at 640 nm as shown in previous research (Wang et al 2016).…”
Section: Visible Light Spectra Of Lignin Solution Mixed With Cbbg Rea...supporting
confidence: 89%
See 4 more Smart Citations
“…3). This indicated that the increase in absorbance at 640 nm in the newly prepared mixtures of alkali lignin solution and CBBG was from a combination of CBBG and lignin; which was consistent with non-covalent combination between the lignins and the CBBG to increase the absorption at 640 nm as shown in previous research (Wang et al 2016).…”
Section: Visible Light Spectra Of Lignin Solution Mixed With Cbbg Rea...supporting
confidence: 89%
“…However, their CBBG mixture absorbance at 460 nm changed less than 5%, when compared to the control mixture absorbance at 460 nm. This indicated that the lignin concentrations in the four kinds of bleaching effluents possibly can be determined via the CBBG method, similar to pulping black liquor (Wang et al 2016).…”
Section: Visible Light Spectra Of Lignin Solution Mixed With Cbbg Rea...mentioning
confidence: 83%
See 3 more Smart Citations